Perlindungan Hukum Terhadap Kekayaan Intelektual Dalam Bisnis Startup - Willy Jayandi Parasian Sinaga; Dewa Gde Rudy (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
The development of technology and information has given rise to more and more startup businesses popping up. This is also accompanied by the existence of intellectual property as a startup business asset which is very important to be protected by law. Intellectual property can be in the form of copyrights, patents, trade secrets and trademarks owned by a startup business. This study aims to find out what legal protection for intellectual property will be in startup businesses, as well as the challenges and obstacles that startup businesses will face to protect their intellectual property. This research is normative with a qualitative approach to several startup business actors and legal policy makers who are involved in the legal protection of intellectual property in startup businesses. The results of the study show that legal protection of intellectual property in startup businesses can be done through registration of copyrights, patents, trademarks, and taking legal action against intellectual property violations. However, startup businesses experience problems in terms of costs and time to register intellectual property rights as well as a lack of legal awareness and knowledge of intellectual property protection. Therefore, there is a need for more intensive outreach and education about intellectual property law protection in startup businesses.